Quality estimation of structurally ordered assembly for threaded connection welding; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 2 - Zhuravlev A. N. (Mathematics and mechanics.Physics, 2007)
Заглавие с титульного листа